A Novel Isothermal Compressed Air Energy Storage System Based on Cooperative Operation of Two-Stage Liquid Piston Units - Yan Cui; Tong Jiang; Hongfei Hou (Energies, 2025)
The transition toward a renewable-based energy structure has significantly accelerated the advancement of energy storage technologies. Compressed air energy storage (CAES) is regarded as a highly promising long-duration energy storage solution due to the advantages of its large scale and long service life. However, the efficiency of conventional compressed air energy storage (CAES) systems remains limited due to the inadequate utilization of thermal energy. Isothermal compressed CAES (ICAES) technology, based on liquid pistons, can overcome the efficiency bottleneck by enabling temperature control during air compression. However, the operation of liquid pistons under high-pressure storage conditions remains a challenge because of the high compression ratio. To enhance the utilization rate of the two-stage liquid piston unit by using the synchronous operations of compression and discharge processes, this paper proposes a coordinated operation scheme. Then, a multi-stage ICAES system under constant-pressure air storage is proposed. Mathematical models and energy efficiency analysis methods of the multi-stage ICAES system are also established. Finally, the operational characteristics are analyzed in combination with the ICAES at 200 kWh. The results show that the proposed system can achieve an overall efficiency of 68.0%, under 85% and 90% efficiencies for low-pressure and linear equipment, respectively. The coordinated operation of the two-stage liquid piston unit can be further extended to multi-stage operations, demonstrating broad application prospects in ICAES systems.